2021
DOI: 10.1038/s41577-021-00542-x
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing monoclonal antibodies for treatment of COVID-19

Abstract: Several neutralizing monoclonal antibodies (mAbs) to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have been developed and are now under evaluation in clinical trials. With the US Food and Drug Administration recently granting emergency use authorizations for neutralizing mAbs in non-hospitalized patients with mild-to-moderate COVID-19, there is an urgent need to discuss the broader potential of these novel therapies and to develop strategies to deploy them effectively in clinical practice, give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
580
1
14

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 664 publications
(602 citation statements)
references
References 85 publications
7
580
1
14
Order By: Relevance
“…We assessed the sensitivity of B.1.617.2 to a panel of human mAbs using the S-Fuse assay. We tested four clinically approved antibodies, Bamlanivimab (LY-CoV555), Etesevimab (LY-CoV016), Casirivimab (REGN10933) and Imdevimab (REGN10987) targeting the RBD 20,36 as well as four other anti-RBD (RBD-48, RBD-85, RBD-98 and RBD-109) and four anti-NTD (NTD-18, NTD-20, NTD-69 and NTD-71) antibodies that were derived from convalescent individuals (Planchais et al, in preparation). Neutralizing anti-SARS-CoV-2 mAbs targeting the RBD can be classified into 4 main categories depending on their binding epitope 35,37 .…”
Section: Neutralization Of B16172 By Monoclonal Antibodiesmentioning
confidence: 99%
“…We assessed the sensitivity of B.1.617.2 to a panel of human mAbs using the S-Fuse assay. We tested four clinically approved antibodies, Bamlanivimab (LY-CoV555), Etesevimab (LY-CoV016), Casirivimab (REGN10933) and Imdevimab (REGN10987) targeting the RBD 20,36 as well as four other anti-RBD (RBD-48, RBD-85, RBD-98 and RBD-109) and four anti-NTD (NTD-18, NTD-20, NTD-69 and NTD-71) antibodies that were derived from convalescent individuals (Planchais et al, in preparation). Neutralizing anti-SARS-CoV-2 mAbs targeting the RBD can be classified into 4 main categories depending on their binding epitope 35,37 .…”
Section: Neutralization Of B16172 By Monoclonal Antibodiesmentioning
confidence: 99%
“…5f). These results have not only suggested that bivalent m31A7 can stabilize the interaction with S protein, thereby providing high avidity, but also highlighted its high affinity comparable to or higher than many other mAbs identified recently 6,42,43 .…”
Section: Identification Of a Broadly Neutralizing Antibody From B Cells Of Mice Immunized With Smgmentioning
confidence: 59%
“…5f). These results have not only suggested that bivalent m31A7 can stabilize the interaction with S protein, thereby providing high avidity, but also highlighted its high affinity comparable to or higher than many other mAbs identified recently 6,42,43 . Taken together, the monoglycosylated S protein (Smg) vaccine has the potential to induce broadly neutralizing antibodies with high affinities.…”
Section: Identification Of a Broadly Neutralizing Antibody From B Cells Of Mice Immunized With Smgmentioning
confidence: 63%
See 1 more Smart Citation
“…A handful of antibody therapies have been granted emergency use authorization by the FDA, over a dozen are in late-stage clinical development, and many more are in preclinical development (17). However, previous efforts to measure the effect of RBD variants on the efficacy of antibody candidates for COVID-19 have mostly been limited to characterizing individual CoV-2 RBD variants on a small number of antibody candidates (8,(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%